(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
The main purpose of this study was to investigate the relationship between income level and corrupt behaviour tendencies among Tertiary Institutions Nonacademic Staff in Calabar Education zone, Cross River State. One research question was formulated and a null hypothesis tested at 0.5 level of significance. Literature was reviewed based on the variable under study, an Ex-post facto research design was adopted and a stratified random sampling technique was used to select four (4) Tertiary Institutions while accidental sampling technique was adopted to select 822 respondents, the population of the study was eight thousand, two hundred and twenty (8220) Nonacademic staff of Tertiary Institutions in Calabar Education Zone. The instrument for data collection was a structured Questionnaire titled Income Level and Corrupt Behaviour Tendencies among Nonacademic Staff Questionnaire (ILCBTNSQ), with Fifteen (15) items. T test was used for test of hypothesis. The data analysis revealed a positive correlation between income and corrupt behaviour tendencies among Nonacademic staff in Calabar Education Zone of Cross River State. Based on the finding, it was recommended that in spite of the fact that prompt payment of salary should be ensued, the government and tertiary institutions should set up a standard criterion that checkmate corruption tendencies among staff in tertiary institutions.